2000
DOI: 10.1021/jm000161d
|View full text |Cite
|
Sign up to set email alerts
|

3-(3,5-Dimethoxyphenyl)-1,6-naphthyridine-2,7-diamines and Related 2-Urea Derivatives Are Potent and Selective Inhibitors of the FGF Receptor-1 Tyrosine Kinase

Abstract: A series of 3-aryl-1,6-naphthyridine-2,7-diamines and related 2-ureas were prepared and evaluated as inhibitors of the FGF receptor-1 tyrosine kinase. Condensation of 4,6-diaminonicotinaldehyde and substituted phenylacetonitriles gave intermediate naphthyridine-2,7-diamines, and direct reaction of the monoanion of these (NaH/DMF) with alkyl or aryl isocyanates selectively gave the 2-ureas in varying yields (23-93%). For the preparation of more soluble 7-alkylamino-2-ureas, a number of protecting groups for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 32 publications
(89 reference statements)
2
37
1
Order By: Relevance
“…[8,9] Further studies revealed that new derivatives of type 3, obtained from modification of the decoration of the lead structure at the 8-position, were endowed with significant cytotoxicity against a panel of cancer cell lines and inhibited selected oncogenic kinases. [10] FGFR-1 and VEGFR-2 kinases inhibitory activities at low nanomolar level were also exhibited by 7-acetamido [1,6]naphthyridines (4) synthetized by Thompson et al [11,12] Chart 1. Structures of [1,6]naphthyridine derivatives 1-4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,9] Further studies revealed that new derivatives of type 3, obtained from modification of the decoration of the lead structure at the 8-position, were endowed with significant cytotoxicity against a panel of cancer cell lines and inhibited selected oncogenic kinases. [10] FGFR-1 and VEGFR-2 kinases inhibitory activities at low nanomolar level were also exhibited by 7-acetamido [1,6]naphthyridines (4) synthetized by Thompson et al [11,12] Chart 1. Structures of [1,6]naphthyridine derivatives 1-4.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives 10 were able to generate high levels of superoxide anion and singlet oxygen, suggesting involvement of both type I and type II oxygen-dependent photosensitization mechanisms. [16] More recently we have studied pyrrolo [3',2':6,7]cyclohepta [1,2-d]pyrimidines (11) and pyrrolo [3',2':6,7]cyclohepta [1,2-b]pyridines (12) which showed very promising antitumor properties. [17,18] Upon photoactivation with light of the proper wavelength, they showed cytotoxic effect at 0.06-4.96 μM and 0.19-10.70 μM respectively, inducing apoptosis associated with rapid and massive production of large amounts of ROS, mitochondrial morphology modifications and activation of lysosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6-Naphthyridines are a class of heterocyclic compounds that exhibit a broad spectrum of biological activities such as inhibitor of HIV-1 integrase [12-15], HCMV [16,17], FGF receptor-1 tyrosine kinase [18], and the enzyme acetylcholinesterase [19]. Many routes for the syntheses of 1,6-naphthyridines derivatives have previously been reported [20-24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, targeted inhibition of FGFR kinases with ATP-competitive small molecule inhibitors has become an attractive therapeutic strategy. Several classes of such inhibitors of have been reported, including indolinones,5 pyrido[2,3-d]pyrimidines,6 napthyridines,7 triazines,8 indenes,9 quinolines,10 and thioindoles 11. However, only a limited number of FGFR inhibitors have entered clinical trials 12-17.…”
mentioning
confidence: 99%